2021
DOI: 10.1021/acsearthspacechem.1c00237
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of Organic Carbon Coatings on Biomass-Burning Particles and Their Role in Reactive Gas Uptake

Abstract: Inorganic salts are a significant component of biomassburning aerosol (BBA) and have inconsistently been observed to undergo chemical reactions with strong acids and other reactants during atmospheric aging, altering particle hygroscopicity and further reactivity while also liberating reactive halides such as ClNO 2 (g) and HCl(g) and recycling or removing nitrogen oxides. The condensation of organic carbon to BBA coemitted by wildfires and other biomass combustion processes can affect aerosol particle reactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…Relative humidity at filter collection times according to back trajectories is in the 60 %-70 % range, which would facilitate aerosol deliquescence and the subsequent uptake of HCl. Previous work (Semeniuk et al, 2007;Jahn et al, 2021) has also shown BBA to uptake water in this RH range. Hydrochloric acid partitioning into aerosol water has also been inferred in urban atmospheres, where the highly water absorbing and soluble chloride in the aqueous phase enhances aerosol water uptake through co-condensation and particle growth, causing haze to form (Gunthe et al, 2021).…”
Section: Marine Aerosolsupporting
confidence: 54%
See 1 more Smart Citation
“…Relative humidity at filter collection times according to back trajectories is in the 60 %-70 % range, which would facilitate aerosol deliquescence and the subsequent uptake of HCl. Previous work (Semeniuk et al, 2007;Jahn et al, 2021) has also shown BBA to uptake water in this RH range. Hydrochloric acid partitioning into aerosol water has also been inferred in urban atmospheres, where the highly water absorbing and soluble chloride in the aqueous phase enhances aerosol water uptake through co-condensation and particle growth, causing haze to form (Gunthe et al, 2021).…”
Section: Marine Aerosolsupporting
confidence: 54%
“…UV exposure can work to break down oligomers and lowvolatility components in organic aerosol (Wong et al, 2015;Lignell et al, 2014) and may account for lower amounts and/or higher volatility of organic aerosol present on CLAR-IFY filters. Photooxidation can also lead to fragmentation of organic chains, and oxidation has been observed to change biomass burning organic aerosol (BBOA) volatility in laboratory studies (Jahn et al, 2021) as well as physical properties (Jahl et al, 2021). Our results of less organic aerosol present for aged samples are consistent with the findings of Dobracki et al (2022) and Sedlacek III et al (2022) of loss of organic aerosol and organic coating with age, although TEM results are caveated by preferential loss of volatile organic material.…”
Section: Organic Aerosolmentioning
confidence: 99%
“…Previous studies found that organic coatings or surface films decrease the reactive uptake of N 2 O 5 on particles. ,,,, Transmission electron microscopy (TEM) analysis of BBA generated during separate experiments that utilized several of the biomass fuels on which we performed kinetics experiments revealed that many particles did indeed contain organic coatings that concealed inorganic salt phases (Figure ). We unfortunately could not obtain TEM/EDX compositional analysis of BBA from all of the fuels used in these kinetics experiments, however, given our extensive microscopy analysis on other BBA samples produced from similar fuels, and previous research on chloride salt phases in BBA, we expect similar core–shell and other complex particle morphologies to be present. ,, Such organic coatings prevalent in BBA would explain the low γ­(N 2 O 5 ) values even in high-chloride fuels in our previous work . However, conducting these experiments above the deliquescence relative humidities of chloride salts expected in BBA seems to allow for the presence of accessible aqueous chloride phases that drive N 2 O 5 hydrolysis.…”
Section: Resultsmentioning
confidence: 84%
“…These are typical of the types of organic aerosol coatings we observed in the BBA we studied and would limit the ability of N 2 O 5 to react with chloride salts. More details and analysis can be found in Jahn et al…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation